Analysis of the Impact of Using Betawi Language in the Speech Structure of Jakarta Adolescents - Iskandarsyah Siregar (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
This research aims to reveal in depth how the influence of the Betawi language influences the speech patterns of teenagers in Jakarta. Through a qualitative and descriptive analytical approach, this research explores words in sentences that show characteristics of Betawi language interference, such as affixation, reduplication, composition, and acronyms. The findings highlight the significant influence of the Betawi language, especially in the areas of affixation and reduplication. For example, words often undergo modification with the addition of Betawi-inspired prefixes, suffixes or confixes, while specific repetition patterns such as 'dwilingga' are also clearly observed. However, interestingly, no Betawi language interference was detected in the formation of compositions and acronyms. This shows the selective influence of the Betawi language on speech morphology, especially influencing affixation and reduplication. This study provides valuable insights for future research into linguistic influences in multi-ethnic and multi-lingual environments such as Jakarta. The implications of this research include a better understanding of language dynamics in linguistically heterogeneous societies, as well as the potential to enrich knowledge about processes of language adaptation and change in complex urban contexts. Thus, this research not only broadens understanding of linguistic phenomena in Jakarta, but also makes an important contribution to the field of linguistic studies.